2011
DOI: 10.1592/phco.31.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Iatrogenic, Excessive, Nondietary Sodium Administration in Patients with Acute Heart Failure Exacerbation on Hospital Length of Stay

Abstract: We observed excessive sodium administration in patients hospitalized for acute exacerbation of heart failure. We speculate that reducing sodium administration in these patents may reduce length of hospital stay and cost of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In a retrospective, single-center analysis of 82 patients admitted to the cardiac intensive care unit for acute HF exacerbation, the mean nondietary sodium load was 4.0±5.0 g/d, which was correlated with an increase in hospital stay. 286 An average of 1.2 g of daily nondietary sodium correlated with hospital stays of up to 5 days, whereas an average of 2.6 g/d led to stays of up to 10 days. 286 Table 6 summarizes the sodium content for both intravenous and oral prescription medications that could be used in the inpatient or outpatient setting.…”
Section: Sodium-containing Medicationsmentioning
confidence: 92%
See 1 more Smart Citation
“…In a retrospective, single-center analysis of 82 patients admitted to the cardiac intensive care unit for acute HF exacerbation, the mean nondietary sodium load was 4.0±5.0 g/d, which was correlated with an increase in hospital stay. 286 An average of 1.2 g of daily nondietary sodium correlated with hospital stays of up to 5 days, whereas an average of 2.6 g/d led to stays of up to 10 days. 286 Table 6 summarizes the sodium content for both intravenous and oral prescription medications that could be used in the inpatient or outpatient setting.…”
Section: Sodium-containing Medicationsmentioning
confidence: 92%
“…286 An average of 1.2 g of daily nondietary sodium correlated with hospital stays of up to 5 days, whereas an average of 2.6 g/d led to stays of up to 10 days. 286 Table 6 summarizes the sodium content for both intravenous and oral prescription medications that could be used in the inpatient or outpatient setting. [287][288][289][290][291][292][293][294][295][296][297][298][299][300][301] oTC MEDiCATionS…”
Section: Sodium-containing Medicationsmentioning
confidence: 92%
“…The impact of nondietary sodium intake on hospital length of stay (LOS) was evaluated in a retrospective study of 182 consecutive patients admitted to a cardiac intensive care unit for acute exacerbation of HF. 30 The mean nondietary sodium load was 4 g/d, predominantly from intravenous administration of 0.9% or 0.45% sodium chloride, and was unrelated to patient age, sex, HF type, or presence of comorbidities. However, daily sodium administration was directly related to the hospital LOS, with an average sodium load of 1.2 g/d corresponding to hospital stays of up to 5 days and an average sodium load of 2.6 g/d correlating with stays of up to 10 days.…”
Section: Drugs Containing Sodium May Adversely Affect Cardiorenal Dismentioning
confidence: 92%
“…Studies have reported that a 50% reduction in the sodium content of drugs given to inpatients would shorten their hospital stay by one day (27) and would decrease the costs of hospitalization due to heart failure by 5.6 billion dollars per year (28,29). According to another report, a 9.5% reduction in sodium intake would result in a decrease in mean systolic pressure by 1.25 mmHg in people aged 40-85 years (26).…”
Section: Discussionmentioning
confidence: 99%